IL-1β Pretreatment Improves the Efficacy of Mesenchymal Stem Cells on Acute Liver Failure by Enhancing CXCR4 Expression. (7th July 2020) - Nie, He; An, Fangmei; Mei, Jie; Yang, Cheng; Zhan, Qiang; Zhang, Qinglin
Abstract : Background . Mesenchymal stem cells (MSCs), with the powerful metabolic and functional supporting abilities for inflammatory diseases, may be an effective therapeutic strategy for acute liver failure (ALF). However, the efficacy of MSCs can still be promoted if pretreatment is applied to enhance their poor migration towards the damaged liver. The purpose of this study is to determine the effect of IL-1 β pretreatment on the efficacy and homing ability of MSCs in ALF. Methods . MSCs were isolated by the whole bone marrow adherence method and characterized. The efficacy and homing ability of IL-1 β -pretreated MSCs (Pre-MSCs) were examined in a rat ALF model and compared with that of MSCs and normal saline. Then, Western blot was performed to detect the c-Met and CXCR4 expression of MSCs and Pre-MSCs and followed by flow cytometry to detect the meaningful indicators. Finally, the migration abilities of different cells and different conditions were tested by the Transwell migration assay. Results . MSCs of ideal purity were successfully isolated and cultured. Comparing with MSCs, Pre-MSCs had significantly better efficacy on improving the survival rate and liver function of ALF rats. Further analyses of damaged liver tissues showed that IL-1 β pretreatment significantly enhanced the efficacy of MSCs on suppressing liver necrosis. Besides, Pre-MSCs exhibited better effects in inhibiting apoptosis and activating proliferation. The results of tracing experiments with CM-Dil-labeled cells confirmed that more cells migrated to the damaged liver in the Pre-MSC group. In terms of mechanism, the CXCR4 expression was significantly enhanced by IL-1 β pretreatment, and an increased migration ability towards SDF-1 that could be reversed by AMD3100 was found in Pre-MSCs. Conclusion . IL-1 β pretreatment could enhance the homing ability of MSCs at least partially by increasing the expression of CXCR4 and further improve the efficacy of MSCs on ALF.